Asian Christian theologies : a research guide to authors, movements, sources - England, John C.; Kuttianittathil, Jose; Prior, John Masford; Quintos, Lily A.; Kwang-Sun, David Suh; Wickeri, Janice (Maryknoll, N.Y. :Orbis Books : [New Delhi]: ISPCK/ Claretian Publishers, 2002)
Contents: v.1. Asia region 17th-20th centuries; South Asia; Austral Asia. v.2. Southeast Asia. v.3. Northeast Asia.
Includes bibliographical references and index
Keywords: Theology, Doctrinal -- Asia; Christianity -- Asia